Does Syndesmotic Fixation Technique Impact Complication Rates and Functional Outcomes Measured by PROMIS Scores Following Operative Repair of Ankle Fractures? - Steven Hadley BA; Rachel Bergman MD; John Peabody MD; Sarah Westvold MPH; Ryan Filler MD; Milap Patel DO; Anish Kadakia MD (Foot & Ankle Orthopaedics)
Submission Type: Ankle Fractures Research Type: Level 3 - Retrospective cohort study, Case-control study, Meta-analysis of Level 3 studies Introduction/Purpose: Various techniques are used to repair the distal tibiofibular syndesmosis. While traditionally performed with syndesmotic screws, recent techniques including the Syndesmosis TightRope® XP (TightRope, Arthrex) and InternalBrace™ (IB, Arthrex) have been developed to optimize natural flexibility and movement of the syndesmosis. It remains unclear whether syndesmotic fixation technique impacts complication rates and outcomes. This study aims to determine which repair technique results in the fewest complications and best functional outcomes as measured by Patient Reported Outcome Measurement Information System (PROMIS) computerized adaptive tests (CATs) of physical function (PF) and pain interference (PI). To our knowledge, this is the largest retrospective study comparing PROMIS scores between these syndesmotic fixation techniques. We hypothesized that Tightrope and IB would reduce complications and improve PROMIS scores compared to screws. Methods: 782 patients who underwent ankle fracture surgery at a single institution between January 2016-December 2021 were reviewed retrospectively. Two foot and ankle fellowship-trained orthopaedic surgeons independently reviewed all radiographs, determined fixation technique, and assessed complications at final follow-up. Multiple extremity injuries, open fractures, and pilon variants were excluded. 328 patients with syndesmotic ruptures were sent post-operative questionnaires. 159 patients with minimum one-year follow-up were analyzed for complications. 70 patients who completed PROMIS CATs were analyzed for functional outcomes. Due to rarity of complications and perfect separation in the data, we were unable to use statistical tests to compare complication incidence across techniques. The Kruskal-Wallis test compared PROMIS scores across repair types. Analysis of PROMIS scores had 80% power to detect large effect sizes (Cohen’s f = 0.40) with a 0.05 significance level but was underpowered for small and medium effects. PROMIS scores were modeled by repair technique using linear regression. Results: 62/159 patients underwent syndesmotic fixation with screw placement, 59/159 with Tightrope, and 38/159 with IB. Overall complication rates with syndesmotic screw fixation were 12.9% (8/62): 8.1% (5/62) degenerative joint disease (DJD), 0% end-stage arthritis, 1.6% (1/62) syndesmotic malreduction, 4.8% (3/62) syndesmotic malunion. Overall complication rate in Tightrope was 1.7% (1/59): 1.7% (1/59) DJD. IB had no radiographic complications. Mean PF was 50.38±9.39 screw, 53.87±9.70 Tightrope, and 52.18±13.08 IB (p=0.71). Mean PI was 49.28±8.22 screw, 47.91±8.80 Tightrope, and 49.15±10.46 IB (p=0.79). Compared to screws, adjusted models demonstrated mean PF 4.00 points greater for Tightrope (p=0.17) and 2.94 points greater for IB (p=0.34). Adjusted models for PI revealed mean scores of 2.05 points less for Tightrope (p=0.42) and 1.23 points less for IB (p=0.65) compared to screws. Conclusion: Our findings indicate that syndesmotic fixation with the Tightrope and IB reduce radiographic complications compared to screws. While this study was underpowered to detect small or medium effect sizes and thus was unable to demonstrate statistically significant differences in PROMIS scores, the higher PF and lower PI for Tightrope and IB compared to screws may reach statistical significance in larger sample sizes. Nevertheless, differences in PF scores in the adjusted model suggest that Tightrope and IB improve PF compared to screw, reaching the lower end range of the minimal clinically important difference for this outcome measure reported in the literature.